DNA methylation in long COVID - Xiao, Yangfan; Vermund, Sten H. (Frontiers in Virology, 2024)
Long COVID (also termed Post-acute sequelae of COVID-19 [PASC]) refers to the chronic symptoms that survivors may experience after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and acute coronavirus disease 2019 (COVID-19) disease. Long COVID represents a global public health, medical, and nursing challenge that affects millions of people. As an emerging and evolving syndrome, long COVID manifests with many combinations of clinical signs and symptoms that healthcare providers and scientists are cataloging and struggling to understand. In this mini-review, we introduce the epigenetic battlefield of DNA methylation (DNAm) on which the virus and the host interact. We suggest ways in which DNAm phenomena and markers induced by this virus-host interaction may help clarify the pathology and prognosis of long COVID. Knowledge of DNAm characteristics of long COVID patients is limited as of this writing (early-2024), investigators have noted both the partial reversibility and the potential long-lasting persistence of the DNAm markers induced by acute COVID-19. Long-term sequelae seen in other coronavirus diseases such as severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) are potential references for long COVID in an effort towards more precise diagnosis and disease characterization, better prediction of outcomes, and the use of epigenetic phenomena towards development of new drugs and immunotherapies.